Consumer culture theory - Thyroff, Anastasia E., 1986-; Murray, Jeff B.; Belk, Russell W. (Research in consumer behavior ;, 2015)
The chapters in this volume are selected from the best papers presented at the 10th Annual consumer culture theory conference held at the University of Arkansas, USA in June 2015. The diverse interpretive research and theory represented in this volume provides the reader with intellectually stimulating opportunities to examine the intersections between a variety of topics that represent the cutting edge in consumer research. These studies draw on an array of qualitative methodologies and the substantive topics represent crucial issues for our times.